Does myth have to be old? Philosophical reflection on myth - Lisiecki, Marcin (Humaniora. Czasopismo Internetowe, 2022)
The present paper is an introduction to the debate on the contemporary methodology of research on myths. I attempt herein to elucidate the essence of myth, with the attempt being carried out in two parts. In the first part, I overview a history of the philosophical debate on the subject as well as I specify the reasons why myth ought to be reunited with truth anew, as was the case with Greek philosophers. In the latter part, I deal with the analysis of myth in relation with a human being – both in the individualist senseand in the social one, with the latter sense performing a significant role in understanding the world as well as humanity at large. Furthermore, I suggest what the essence of myth might be and what validity it can have for the contemporary man. The reflection included in the present text is inspired by some pertinent philosophical conceptions that allow me to show that it is possible to say something new about myth and the research thereupon.